Perceived helpfulness of treatment for posttraumatic stress disorder: Findings from the World Mental Health Surveys. Issue 10 (15th July 2020) - Stein, Dan J.; Harris, Meredith G.; Vigo, Daniel V.; Tat Chiu, Wai; Sampson, Nancy; Alonso, Jordi; Altwaijri, Yasmin; Bunting, Brendan; Caldas‐de‐Almeida, José Miguel; Cía, Alfredo; Ciutan, Marius; Degenhardt, Louisa; et al.
Abstract: Background: Perceived helpfulness of treatment is an important healthcare quality indicator in the era of patient‐centered care. We examine probability and predictors of two key components of this indicator for posttraumatic stress disorder (PTSD). Methods: Data come from World Mental Health surveys in 16 countries. Respondents who ever sought PTSD treatment ( n = 779) were asked if treatment was ever helpful and, if so, the number of professionals they had to see to obtain helpful treatment. Patients whose treatment was never helpful were asked how many professionals they saw. Parallel survival models were estimated for obtaining helpful treatment in a specific encounter and persisting in help‐seeking after earlier unhelpful encounters. Results: Fifty seven percent of patients eventually received helpful treatment, but survival analysis suggests that it would have been 85.7% if all patients had persisted in help‐seeking with up to six professionals after earlier unhelpful treatment. Survival analysis suggests that only 23.6% of patients would persist to that extent. Odds of ever receiving helpful treatment were positively associated with receiving treatment from a mental health professional, short delays in initiating help‐seeking after onset, absence of prior comorbid anxiety disorders and childhood adversities, and initiating treatment before 2000. Some of these variables predicted helpfulness of specific treatment encounters and others predicted persistence after earlier unhelpful encounters. Conclusions: The great majority of patients with PTSD would receive treatment they considered helpful if they persisted in help‐seeking after initial unhelpful encounters, but most patients whose initial treatment is unhelpful give up before receiving helpful treatment.